Impact of Economic Crises on Financial Stability and Liquidity of Slovak Local Self-Governments - Viera Papcunová; Monika Hudáková; Jarmila Hudáková; Michal Levický (Transylvanian Review of Administrative Sciences, 2025)
Evaluating the effectiveness of local self-governments is a very complex process due to the fact that local self-governments are not primarily supposed to make a profit, but to provide services to residents that will contribute to improving their quality of life. To improve the performance of local self-governments, it is important to consciously and gradually introduce modern management methods successfully applied in the private sector to increase the efficiency and quality of the services provided. One of these methods is financial analysis. Therefore, the article focuses on the assessment of the impact of selected debt ratio indicators on the overall liquidity of the Slovak local self-governments in the period of 2010-2023. At the same time, the analysis focused on the assessment of the impact of the financial crisis and the Covid-19 pandemic period on the overall liquidity of local self-governments. The results of the analyses proved that the selected indicators showed a fluctuating trend, with the most significant impact on the overall liquidity of local self-governments being the level of indebtedness and the return on assets of local self-governments. Overall liquidity increased in the Covid-19 pandemic period compared to the period when local self-governments were affected by the economic crisis.